Software development for embedded systems - Bapoo, Hansraj (My University, 2016)
This report examines the major factors influencing the development of embedded systems. The discussion covers, among other aspects, features of embedded systems that are common to software development in general, the main characteristics of embedded systems, some of the current development strategies, the mlcrocontroller market, language issues and development tools. Following the assessment study and a practical embedded system development, the report concludes that although: I embedded systems are typified by relatively few lines of codes, their complex nature necessitates the application of a disciplined development approach. The report presents a riskbased hardware-software co-design development approach in an attempt to reconcile the existing formal development models to the technical realities of embedded systems. A practical embedded system case study is presented, It involves the development of a microcontroller-based system for the three-phase inverter of an uninterruptible power supply (UPS).
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 1996.
Keywords: Computer software -- Development.; Embedded computer systems.